Pengaruh Gaya Kepemimpinan Kompetensi Dan Disiplin Kerja Terhadap Kinerja Pegawai Negeri Sipil Pada Dinas Kebudayaan Kota Denpasar - Ni Made Ayu Yulyantini; I Gusti Putu Agung Widya Goca (Baca Dulu Publisher, 2024)
The purpose of this study was to examine the interplay between leadership style, competency, and work discipline, and how these influence the performance of public employees in the Denpasar City Culture Service. Saturated sampling was utilized to choose 31 workers from the Denpasar City Culture Service to participate in this study's population. Validity, reliability, classical assumption testing, multiple linear regression, coefficient of determination testing, t tests, and F tests were utilized to analyze the data in this research. It is clear from the study's findings that (1) leadership style has a beneficial and statistically significant impact on productivity in the workplace. A competent workforce is more productive and successful. Thirdly, a well-disciplined workplace significantly improves productivity. Employee performance is positively impacted by leaders' styles, abilities, and work discipline at the same time. There is a 72.9% level of effect from external factors on employee output.